Radiation Synthesis and Characterization of Conducting Polyaniline and Polyaniline/Silver Nanoparticels - Omer, Mohammed Ahmed Ali (2007)
The conducting polymer PANI nanoparticles were synthesized from polyvinyl alcohol PVA and aniline hydrochloride (AniHCl) blend films at different AniHCl monomer concentrations (0.5, 1.0, 1.5 and 2.0 g or as 9.0, 16.7, 23.1, and 28.6 wt %) and irradiated with gamma radiation at different doses (0, 10, 20, 30, 40, and 50 kGy) at ambient conditions. Upon irradiation AniHCl undergoes dechlorination by the loss of Cl– that acts as an oxidant and ‘in situ’ polymerizing aniline into conducting PANI nanoparticles. The formation of conducting PANI has been observed by the change of colour from colourless to dark green due to the formation of polaron species characterized by the defect in molecular structure of the polymer and was confirmed by Raman scattering at 1637 cm-1 Raman shift assigned for C=N stretching of imines group. The SEM morphology of PVA/PANI composites reveals the spherical structure of nanoparticles, 50 – 100 nm in diameter which then transformed into globular clusters of conducting PANI with good environmental stability. The optical properties of PANI nanoparticles were measured by means of UV-visible spectrophotometry and found that the absorbance at 790 nm band of conducting PANI increased exponentially with the increase of dose and fitted the expression of the form: exp( / ) 0 0 y y D D , where D is the absorbed dose and 0 D is the dose sensitivity. The results reveal that the optical parameters such as absorption edge, activation energy, and band gap energy decreased with the increase of dose and AniHCl concentration. When the dose increased from 10 kGy to 50 kGy the absorption edge decreased from 1.0 to 0.91 eV for 9.0% AniHCl and from 0.82 to 0.44 eV for 28.6% AniHCl, the activation energy decreased from 2.25 to 1.5 eV for 9.0% AniHCl and from 0.8 to 0.69 eV for 28.6% AniHCl, and the band gap energy decreased from 1.36 to 1.18 eV for 9.0% AniHCl and from 1.12 to 1.00 eV for 28.6 wt% AniHCl. The electrical conductivity was determined by an impedance analyzer and found the conductivity increased with the increase of dose and AniHCl concentration. The conductivity is mainly the direct current (dc) component attributed to the creation of polarons in the PANI structure and they are the charge carriers of conducting PANI which are set in motion in a form of electron hopping within the backbone of the composites. The dc conductivity increased from 5.75106S/m to 1.32 103 S/m for 9.0 wt% and from 7.76105 S/m to 1.17 10 1 S/m for 28.6 wt% AniHCl when the dose was increased from 10 kGy to 50 kGy. The dc conductivity is therefore governed by the exponential relation of the form: exp( / ) 0 0 D D dc   , where 0  and 0 D were found varied with different AniHCl concentration.The silver nanoparticles were synthesized from PVA/silver nitrate (AgNO3) blend films at different AgNO3 dopant concentration of 0.01 wt % and irradiated with gamma radiation at different doses (0, 10, 20, 30, 40, and 50 kGy) at ambient conditions. Upon gamma irradiation, the released electrons interact with silver ions Ag+ which reduce to silver nanoparticles Ag0. The formation of Ag0 nanoparticles has been observed by the colour changed from colourless to golden yellow due to the presence of Ag0 nanoparticles and was confirmed by XRD analysis. Further, the presence of metal nanoparticles was verified with the UV-visible absorption measurement that reveals the absorption peak at 425 nm due to surface plasmon resonant phenomenon at the conduction band of Ag0 nanoparticles where the absorbance increased with the increase of dose and fitted the expression of the form: exp( / ) 0 0 y y D D . The composites of PVA/PANI/Ag0 nanoparticles were radio-synthesized with the concentration of AniHCl at 28.6 wt%. The concentrations of AgNO3 dopant are different (0.01, 0.03, 0.05, and 0.07 wt %) and different radiation doses (0, 10, 20, 30, 40, and 50 kGy). The results from optical absorption measurement reveal two absorption bands at 415 nm due to surface plasmons of Ag0 nanoparticles and at 600 nm due to polarons of low conducting PANI. The absorption band shifted from 425 nm to 415 nm crrosponds to decreasing diameter of Ag0 nanoparticles in the presence of PANI in the composites. The band gap increased with the increase of AgNO3 dopant, from 1.72 eV for 0.01 wt% to 2.58 eV for 0.07 wt% dopant irradiated at 50 kGy. The dc conductivity increased with the increase of dose and decreased with the increase of dopant concentration Ag+. The dc conductivity for 0.01 wt% dopant increased from 9.77 106 S/m at 10 kGy to 8.51104S/m at 50 kGy. For dopant concentration at 0.07 wt%, however, the dc conductivity increased from 1.07 10 7 S/m at 10 kGy to 1.23 105 S/m at 50 kGy. The dc conductivity of PVA/PANI/Ag0 nanocomposites was found to have an exponential expression of the form: exp( / ) 0 0 D D dc   .